The Influence of Political Willingness, Flypaper Effect, and Regional Original Revenue on Regency/City Regional Expenditure in Central Java - Dwi Nur Rahmawati; Suyatmin Waskito Adi (Universitas KH. Abdul Chalim Mojokerto, 2025)
Public financial management requires more attention because it is closely related to the prosperity of the nation, as stipulated in the 1945 Constitution Article 23 paragraph (1) which states that the APBN must be managed transparently and responsibly for the welfare of the people. Indonesia's fiscal decentralization policy gives greater authority to local governments to manage budgets to improve public services and regional development. The focus of this study is on regional expenditure, which is defined as a reduction in net assets during a certain period to fulfill regional obligations. In accordance with Government Regulation No. 58/2005, regional expenditures are used to fund mandatory, optional, and concurrent government affairs, and are classified based on affairs, functions, and expenditure groups. This study aims to analyze the effect of Political Willingness, the Flypaper Effect Phenomenon, and Regional Original Revenue on Regency / City Regional Expenditure in Central Java Province for the 2019-2023 Period. this research uses multiple regression analysis methods. It can be seen that the variables of Political Willingness, Flypaper Effect Phenomenon, and Regional Original Income have a positive and significant effect on Regional Expenditure.